(untitled) (Bangladesh Journal of Zoology, 2015)
Developmental period of the pteromalid wasp Anisopteromalus calandrae, was observed in the laboratory using two types of hosts at different constant temperature and relative humidity. The developmental period ranged from 28.6 ± 6.6 days at 20°C temperature and 90% R.H. to 10.7 ± 2.1 days at 35°C and 90% R.H. Mating of the adult parasites occurred shortly after emergence at all the temperature regimes and relative humidities under study period. The female started laying eggs within 1 day at 25, 30 and 35°C and in about 1.5 2.0 days at 20°C. Relative humidity had no appreciable effect on oviposition. The incubation period was 2.1 ± 0.1 days at 20°C and 50% R.H. The larval period decreased from 9.3 ± 0.1 days at 20°C to 3.2 ± 0.1 days at 35°C. The relative humidity played no pronounced effect on the larval durations. The developmental period from egg to adult with Rhizopertha dominica as host was found to be shorter, being approximately one day less than that of S. oryzae as host. The duration of developmental period of male was less than that of female irrespective of temperatures and relative humidity conditions. The pupal period in female individuals decreased from 15.5 ± 0.1 days at 20ºC to 5.1 ± 0.1 days at 35ºC. The variations in relative humidity at different constant temperatures lengthened the pupal period to a lesser extent as was revealed form the experiments performed. Bangladesh J. Zool. 41(1): 87-96, 2013